2004
DOI: 10.1088/0951-7715/18/1/018
|View full text |Cite
|
Sign up to set email alerts
|

The structure of equilibrium solutions of the one-dimensional Doi equation

Abstract: We analyse the structure of steady state solutions of the one-dimensional Doi model for rod-like molecules. We prove that if the interaction strength parameter U is less than 4, then the constant solution is the only possible steady state solution. If U is larger than 4, then there is a new solution that corresponds to the nematic phase. All other non-constant solutions are obtained from this solution by translation. We prove further that the nematic solutions have period π instead of 2π , a property that sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 9 publications
4
53
0
Order By: Relevance
“…which contradicts with (25). Thus the claim is established: (q (1) 1 , q (1) 2 ) and (q (2) 1 , q (2) 2 ) must be the same.…”
Section: Stability Analysismentioning
confidence: 86%
“…which contradicts with (25). Thus the claim is established: (q (1) 1 , q (1) 2 ) and (q (2) 1 , q (2) 2 ) must be the same.…”
Section: Stability Analysismentioning
confidence: 86%
“…However, it is widely accepted that the Maier-Saupe potential affords sufficient degrees of freedom to capture the dynamics of the micro-micro interaction. In a recent development, the bifurcation diagram for the Onsager equation (and therefore also Smoluchowski equation) with the Maier-Saupe potential was confirmed rigorously (see [5], [6], [8], [13], [18], [19]). The equation undergoes two bifurcations.…”
Section: Introductionmentioning
confidence: 90%
“…It has been shown that the equilibrium solution of the Smoluchowski equation is given by the Boltzmann distribution [6,7,8,12,21,22,26,11,25] ρ(m) = 1…”
Section: Equilibria Of Smoluchowski Equation For Magnetic Dispersionsmentioning
confidence: 99%